2010
DOI: 10.1177/230949901001800304
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Proximal Femur in a Pakistani Population

Abstract: Morphology of the proximal femur in our study population differed significantly from those in western populations, indicating regional variation. It could also be due to the younger age of our population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 8 publications
4
37
0
Order By: Relevance
“…In 150 healthy patients, Lecerf et al (2009) obtained an average FNA of 129º (± 6º). Likewise, Umer et al (2010) obtained similar results in the Pakistani population, where the femoral neck angle was on average 130.3mm (± 6.1 mm). Calis et al (2004) observed in x-rays of Turkish female patients that the width of the femoral neck was 35 mm, along with an angle of 128.9º.…”
Section: Discussionsupporting
confidence: 67%
“…In 150 healthy patients, Lecerf et al (2009) obtained an average FNA of 129º (± 6º). Likewise, Umer et al (2010) obtained similar results in the Pakistani population, where the femoral neck angle was on average 130.3mm (± 6.1 mm). Calis et al (2004) observed in x-rays of Turkish female patients that the width of the femoral neck was 35 mm, along with an angle of 128.9º.…”
Section: Discussionsupporting
confidence: 67%
“…The dimensions of the femur are affected by gender and ethnicity [8,16,20,26,31,40,43,44]. Other than a small correlation between increased height and increased AP femoral head symmetry, there was no association between asymmetry and age, weight, height, ethnicity, and gender.…”
Section: Discussionmentioning
confidence: 94%
“…Proximal femoral anatomy has been the subject of numerous studies owing to the success of hip arthroplasty worldwide [5,6,15,18,31,43], and as a result of the discovery that certain femoral disorders, such as femoral acetabular impingement and Legg-Calvé-Perthes disease, can lead to osteoarthritis [1,11,13,41]. The investigators who have examined symmetry have studied bone properties and cortex thickness [28,32,36,40], with few studying dimensions [3,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,12] In this study, the inner and outer diameters of the stainless steel cylinder representing lesser trochanteric level were 30 mm and 45 mm on the level of lesser trochanter. [17][18][19][20] Two centimeters below the tip of the stainless steel cylinder, there were two opposite holes with a diameter of 8 mm. In the three-point bending test, we used an interlocking nail of 380x12 mm, the proximal 90 mm part of which was 13 mm in diameter There was an oblong proximal locking screw hole which was 12 mm long and 6 mm wide 60 mm distal from the interlocking nail proximal edge.…”
Section: Methodsmentioning
confidence: 99%